Insulin-Like Growth Factor 1 Regulates Acute Inflammatory Lung Injury Mediated by Influenza Virus Infection - Li, Guiping; Zhou, Lijuan; Zhang, Can; Shi, Yun; Dong, Derong; Bai, Miao; Wang, Rong; Zhang, Chuanfu (Frontiers in Microbiology, 2019)
The acute inflammatory lung injury is an important cause of death due to influenza A virus (IAV) infection. Insulin-like growth factor 1 (IGF1) played an important role in the regulation of inflammation in the immune system. To investigate the role of IGF1 in IAV-mediated acute inflammatory lung injury, the expression of IGF1 and inflammatory cytokines were tested after IAV A/Puerto Rico/8/1934 (H1N1) (abbreviated as PR8) infection in A549 cells. Then a BALB/c mouse model of PR8 infection was established. On 3d, 5d, 7d, and 9d post-infection, the mice lung tissue was collected to detect the expression changes in IGF1 mRNA and protein. The mice were divided into four groups: 1) PBS (abbreviation of phosphate buffered saline); 2) PR8 + PBS; 3) PR8 + IGF1; and 4) PR8 + PPP (abbreviation of picropodophyllin, the IGF1 receptor inhibitor). The body weight and survival rate of the mice were monitored daily and the clinical symptoms of the mice were recorded. On 5d post-infection, the mice were sacrificed to obtain the serum and lung tissues. The expression of inflammatory cytokines in the serum was detected by enzyme linked immunosorbent assay, lung injury was observed by hematoxylin-eosin staining, the viral proliferation in the lung was detected by real-time quantitative PCR, and the protein expression of the main molecules in the phosphatidylinositol-3-kinases/protein kinase B (PI3K/AKT) and mitogen-activated protein kinase (MAPK) signaling pathways were detected by Western blot. It was found that IGF1 expression is upregulated in A549 cells and BALB/c mice infected with PR8, whereas IGF1 regulated the expression of inflammatory cytokines induced by PR8 infection. Overexpression of IGF1 aggravated the IAV-mediated inflammatory response, whereas the inhibition of IGF1 receptor reduced such inflammatory response. The phosphorylation of IGF1 receptor triggered the PI3K/AKT and MAPK signaling pathways to induce an inflammatory response after IAV infection. Therefore, IGF1 plays an important immune function in IAV-mediated acute inflammatory lung injury. IGF1 may provide a therapeutic target for humans in response to an influenza outbreak, and inhibition of IGF1 or IGF1 receptor may represent a novel approach to influenza treatment.